Accounting information quality and decision-usefulness of governmental financial reporting: Moving from cash to modified cash. Issue 1 (10th April 2017) - Cohen, Sandra; Karatzimas, Sotirios
Abstract : Purpose: This paper aims to provide an assessment of the decision-usefulness and quality of governmental financial reports in Greece under the recently adopted modified-cash basis. The evaluation is performed within the wider debate regarding the actual benefits of a transition toward an accounting paradigm that lies closer to accrual accounting as the Greek modified-cash basis borrows several accrual characteristics. Design/methodology/approach: The transition to modified accruals is analyzed through the prism of the new institutional theory. The approach adopted builds on the characteristics of the accounting information pertaining to the conceptual frameworks of public and private sector accounting standard setting bodies. The assessment is conducted on the basis of the perceptions of public sector financial information users on a Web-based questionnaire. Findings: The findings provide empirical evidence, albeit of moderate magnitude, in favor of the benefits associated with a move to full accruals. Originality/value: The study moves the debate on the merits of accounting systems' changes toward the worldwide witnessed trajectory a step forward by providing practical evidence on the matter.